Conducta Obstétrica en multípara de 32 años con 38 semanas de gestación más desprendimiento placentario. - Acurio Falcón, Yessica Del Roció (2021)
Placental abruption is an important cause of maternal and fetal morbidity and mortality. It can be an obstetric emergency. Manifestations may include vaginal bleeding, spontaneous or palpable uterine pain, hemorrhagic shock, and disseminated intravascular coagulation. The diagnosis is clinical and sometimes ultrasound. A case of moderate placental abruption is presented in a 32-year-old pregnant woman with a 38-week gestation, first warning signs were contractile-type abdominal pain radiating to the lumbar area in a moderate way with an approximation of p hours of evolution showing loss of vaginal bleeding. The diagnosis is clinical and sometimes ultrasound. Treatment is modified activity for mild symptoms and early induction of labor for maternal or fetal instability or in a near-term pregnancy.